Dětství v otroctví pohledem dobových ego-dokumentů - Šárka Bubíková (Theatrum Historiae)
The article introduces the specific kind of American ego-documents – the so-called slave narratives – and uses them to discuss the experience of childhood spent in slavery. It further contrasts the reality of slave childhood with the period’s idealization of childhood as a fragile state of innocence, purity and joyfulness and mentions how this contrast was used by the abolitionist movement.